Early myopathy in Duchenne muscular dystrophy is associated with elevated mitochondrial H2O2 emission during impaired oxidative phosphorylation. Issue 3 (2nd April 2019) - Hughes, Meghan C.; Ramos, Sofhia V.; Turnbull, Patrick C.; Rebalka, Irena A.; Cao, Andrew; Monaco, Cynthia M.F.; Varah, Nina E.; Edgett, Brittany A.; Huber, Jason S.; Tadi, Peyman; Delfinis, Luca J.; Schlattner, U.; et al.
Abstract: Background: Muscle wasting and weakness in Duchenne muscular dystrophy (DMD) causes severe locomotor limitations and early death due in part to respiratory muscle failure. Given that current clinical practice focuses on treating secondary complications in this genetic disease, there is a clear need to identify additional contributions in the aetiology of this myopathy for knowledge‐guided therapy development. Here, we address the unresolved question of whether the complex impairments observed in DMD are linked to elevated mitochondrial H2 O2 emission in conjunction with impaired oxidative phosphorylation. This study performed a systematic evaluation of the nature and degree of mitochondrial‐derived H2 O2 emission and mitochondrial oxidative dysfunction in a mouse model of DMD by designing in vitro bioenergetic assessments that attempt to mimic in vivo conditions known to be critical for the regulation of mitochondrial bioenergetics. Methods: Mitochondrial bioenergetics were compared with functional and histopathological indices of myopathy early in DMD (4 weeks) in D2.B10‐DMD mdx /2J mice (D2. mdx )—a model that demonstrates severe muscle weakness. Adenosine diphosphate's (ADP's) central effect of attenuating H2 O2 emission while stimulating respiration was compared under two models of mitochondrial‐cytoplasmic phosphate exchange (creatine independent and dependent) in muscles that stained positive for membrane damage (diaphragm, quadriceps, and white gastrocnemius). Results: Pathway‐specific analyses revealed that Complex I‐supported maximal H2 O2 emission was elevated concurrent with a reduced ability of ADP to attenuate emission during respiration in all three muscles (mH2 O2 : +17 to +197% in D2. mdx vs. wild type). This was associated with an impaired ability of ADP to stimulate respiration at sub‐maximal and maximal kinetics (−17 to −72% in D2. mdx vs. wild type), as well as a loss of creatine‐dependent mitochondrial phosphate shuttling in diaphragm and quadriceps. These changes largely occurred independent of mitochondrial density or abundance of respiratory chain complexes, except for quadriceps. This muscle was also the only one exhibiting decreased calcium retention capacity, which indicates increased sensitivity to calcium‐induced permeability transition pore opening. Increased H2 O2 emission was accompanied by a compensatory increase in total glutathione, while oxidative stress markers were unchanged. Mitochondrial bioenergetic dysfunctions were associated with induction of mitochondrial‐linked caspase 9, necrosis, and markers of atrophy in some muscles as well as reduced hindlimb torque and reduced respiratory muscle function. Conclusions: These results provide evidence that Complex I dysfunction and loss of central respiratory control by ADP and creatine cause elevated oxidant generation during impaired oxidative phosphorylation. These dysfunctions may contribute to early stage disease pathophysiology and support the growing notion that mitochondria are a potential therapeutic target in this disease.